Field Implementation of Climate-Smart Integrated Small Ruminant Innovations (Smart Pack) - Haile, Aynalem; Getachew, Tesfaye; Belay, Berhanu; Rekik, Mourad; Rischkowsky, Barbara A. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Small ruminant value chain development started in Ethiopia as part of Livestock and Fish CRP in 2012, and then continued since 2017 as Livestock CRP, in seven sites representing different regions of Ethiopia, production systems and communities. The objective of the initiative was to test technological and institutional innovations that would transform the small ruminant value chain and this involved rigorous procedures. Over the years, we have pilot tested many innovations along the small ruminant value chain which were found to be technically sound to be implemented, financially feasible and resulted in improvement of the livelihood of communities. Most of the proven technologies were also evaluated from environmental sustainability lens too focusing on sustainably increasing small ruminant productivity and incomes, adapting, and building resilience to climate change and reducing greenhouse gas emissions, where possible. Therefore, we believe the technologies were ready to scale. As part of the Accelerating the Impact of CGIAR Climate Research in Africa (AICCRA), we are facilitating the scaling of these innovations through various mechanisms. One such approach is to demonstrate the framework on the ground, on scaling of these climate smart small ruminant innovation packages involving research and extension systems in Ethiopia. For the purpose we identified, through a consultative process, three sheep value chain sites (Bonga, Doyogena and Menz) and one goat (konso) site. In each site we selected few villages (table 1) where we tested the framework. Our institutional arrangement involved the establishment of breeder/ producer cooperative for each village. More than 7500 people directly benefited from the implementation. The details of what has been done and achieved for each site is described below.